2012
DOI: 10.4055/cios.2012.4.4.313
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Plate Osteosynthesis for Open Fractures of the Proximal Tibia

Abstract: BackgroundRelatively few studies have addressed plate osteosynthesis for open proximal tibial fractures by now. The purpose of this study was to assess the results of minimally invasive plate osteosynthesis (MIPO) for open fractures of the proximal tibia.MethodsThirty-four patients with an open proximal tibial fracture were treated by MIPO. Thirty of these, who followed for over 1 year, constituted the subject of this retrospective study. According to the AO Foundation and Orthopaedic Trauma Association (AO-OT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 21 publications
2
38
0
3
Order By: Relevance
“…Feng et al [9] reported good results when fixed with LCP in comparison with dynamic compression plate (DCP) with an additional benefit of minimally invasive surgery. Kim et al [10] reported good results with MIPPO technique in treatment of open proximal tibial fractures with adequate soft tissue coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Feng et al [9] reported good results when fixed with LCP in comparison with dynamic compression plate (DCP) with an additional benefit of minimally invasive surgery. Kim et al [10] reported good results with MIPPO technique in treatment of open proximal tibial fractures with adequate soft tissue coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, surgical approaches using less invasive plate osteosynthesis have been used in various fracture surgeries to diminish soft tissue complications and promote biologic bone healing [3,17,28]. Although the less invasive technique has shown to have fewer soft tissue complications, faster union, and better cosmesis [6,17,19,21,28], it has never been devised to use in opening-wedge high tibial osteotomy.…”
Section: Introductionmentioning
confidence: 99%
“…Although the less invasive technique has shown to have fewer soft tissue complications, faster union, and better cosmesis [6,17,19,21,28], it has never been devised to use in opening-wedge high tibial osteotomy.…”
Section: Introductionmentioning
confidence: 99%
“…A high success rate and good clinical results from the MIPO technique have been reported in patients with distal tibial metaphyseal fractures [2,[7][8]. Although this technique has many advantages, several complications have been reported, such as skin irritation overlying the plates, skin necrosis, and plate exposure [2,[9][10][11][12]. Little has been reported about postoperative complications of the MIPO technique in patients with distal tibial metaphyseal fractures.…”
Section: Introductionmentioning
confidence: 99%